The Semivariance-Minimizing Hedge Ratio - Calum G. Turvey; Govindaray Nayak (Journal of Agricultural and Resource Economics, 2003)
This study presents a new approach to the optimal hedging decision. In some empirical studies, the standard hedge using the mean-variance hedge ratio provides results which are inconsistent with downside risk management. The new approach taken here relates the optimal hedge ratio to semivariance rather than variance. An algorithm to solve for the minimum semivariance hedge is presented, and applied to hedging Kansas City wheat and Texas steers.